2012
DOI: 10.7317/pk.2012.36.5.579
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Electrical Conductivity of Polystyrene/Carbon Nanotube Microcellular Foams Polymerized by High Internal Phase Emulsions

Abstract: Polystyrene/carbon nanotube (CNT) microcellular foams were prepared to have electrically conductive properties via high internal phase emulsion polymerization. In this study, we have investigated the effects of surface modification of CNT, surfactant content and dispersion time to improve the stability of emulsion and the electrical conductivity of foam. Acid treatment and a surfactant were used to effectively disperse CNTs in the aqueous phase. In the organic phase, CNTs were used after a surface modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Noh et al. had reported higher electrical conductivity of foams when CNTs were dispersed in the aqueous phase of HCEs . It was assumed that the dispersed CNTs in the aqueous phase could form an efficient two-dimensional network on the cell surface after the polymerized monolith becomes dry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noh et al. had reported higher electrical conductivity of foams when CNTs were dispersed in the aqueous phase of HCEs . It was assumed that the dispersed CNTs in the aqueous phase could form an efficient two-dimensional network on the cell surface after the polymerized monolith becomes dry.…”
Section: Introductionmentioning
confidence: 99%
“…Noh et al had reported higher electrical conductivity of foams when CNTs were dispersed in the aqueous phase of HCEs. 44 It was assumed that the dispersed CNTs in the aqueous phase could form an efficient two-dimensional network on the cell surface after the polymerized monolith becomes dry. By contrast, CNTs have to form a three-dimensional (3D) network structure inside the polymerized matrix of the foam if it is dispersed in the organic phase and hence requires a higher concentration of CNTs.…”
Section: Introductionmentioning
confidence: 99%